The relationship between pleural effusion index and mortality in children with dengue shock syndrome - Novianti Hawarini; Muhammad Sholeh Kosim; Mohammad Supriatna; Yusrina Istanti; Eddy Sudjanto (Indonesian Pediatric Society Publishing House, 2012)
Background Dengue shock syndrome (DSS) mortality rate is still high. The extent of plasma effusion in dengue shock syndrome can be identified in the right lateral decubitus position on chest x􀁃ray, and quantified by the pleural effusion index (PEl). It is thought that PEl value can be used to predict DSS mortality in children. Pleural effusion in DSS patients can cause respiratory failure and death. Objective To determine the relationship bet ween PEl and mortality in children \\lith DSS. Methods This cross􀁃sectional, retrospective study was held in the Dr. Kariadi Hospital, Semarang, Indonesia. Data was taken from medical records of pediatric intensive care unit (PICU) patients with DSS from January 2009 to January 2011. DSS diagnosis was confirmed by clinical and radiological manifestations. PEl diagnosis was established by the presence of fluid in the pleural cavity on pulmonary radiological examinations. X􀁃rays were interpreted by the radiologist on duty at the time. Chi square and logistic regression tests were used to analyze the data. Results There were 48 subjects with DSS, consisting of 18 males (37.5 %), and 30 females (62.5%). Twenty􀁃nine subjects (60.4%) survived and 19 (39.6%) died. One patient (2.1 %) had PEl <6%, 4 (8.3%) had PEl 6-15%, 17 (35.4%) had PEl 15-30%, and 26 (54.2%) had PEl> 30% on their x􀁃rays. The mortality rate of DSS with PEl 15-30% was 11.8% (95% CI 0.021 to 0.564; P<0.005) and PEl >30% was 65.4 % (95% CI 3,581 to 99,642; P <0.005). Cone-lution PEl> 15% was a risk factor for mortality in children with DSS. [Paediatr lndanes. 2012;52:239-42].